Régimen de percepciones a las importaciones y su incidencia en la situación financiera de la empresa HR. SUPPLIES E.I.R.L., distrito de Trujillo, año 2017 - Ramos Leiva, Deivid Steven (2018)
The current research work aims to determine the effect of the Imports Collection Regime appliance on the HR. SUPPLIES E.I.R.L. company’s Financial Position in Trujillo district, during 2017. For such purpose, HR. SUPPLIES E.I.R.L. company’s Financial Position is evaluated being both on a scenario in which the Imports Collection Regime is applicated and on another one in which the same Regime is not applicated; in order to show the effects generated by said IGV Advance Payment System. Therefore, it has gathered financial information as well as documentation with regard to imports which were made by the company under study for 2017; likewise, it has been made interviews directed to the company’s employees. In that regard, in application of several methods of financial analysis as well as the deployment of ratios or financial indicators, it was posible to analyze and evaluate the unfavourable effects caused on HR. SUPPLIES E.I.R.L. company’s Financial Position by the Imports Collection Regime. As a result of the current reasearch work, it concludes the Imports Collection Regime affects negatively the HR. SUPPLIES E.I.R.L. company’s Financial Position; given that the liquidity level with a cash-in-hand reduction of 17.34%, equally the leverage level with a short-term financial obligations increase of 11.11%, and likewise the financial performance with a 2017 net profit decrease of 10.48% are adversely affected.